2020
DOI: 10.1111/ajd.13303
|View full text |Cite
|
Sign up to set email alerts
|

Support for a Microbial Basis for Hyperkeratotic Flexural Erythema

Abstract: summer. Increased outdoor activity during warmer weather and subsequent direct exposure to soil (e.g. through gardening) and/or insect vectors (when less clothing is worn) are possible sources of transmission in these cases. Furthermore, a potential zoonotic cycle with possums has been postulated to be involved in the expansion of M. ulcerans infections. 2,6 These mammals are commonly seen in urban Melbourne parks and suburbs thus could act as a reservoir for the infection which can be transmitted to humans, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The next most commonly implicated precipitant was benzalkonium chloride, a quaternary ammonium cationic detergent found in household laundry detergents. This, combined with reported resolution observed following treatment with systemic antibiotics, has lent support to the role of an altered microbiome in the development of granular parakeratosis 3,14–16 . However, rare reports of congenital onset, and development of granular parakeratosis following administration of systemic medications, highlight that the exact pathogenesis remains elusive and is a subject that warrants further investigation 17–19 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The next most commonly implicated precipitant was benzalkonium chloride, a quaternary ammonium cationic detergent found in household laundry detergents. This, combined with reported resolution observed following treatment with systemic antibiotics, has lent support to the role of an altered microbiome in the development of granular parakeratosis 3,14–16 . However, rare reports of congenital onset, and development of granular parakeratosis following administration of systemic medications, highlight that the exact pathogenesis remains elusive and is a subject that warrants further investigation 17–19 …”
Section: Discussionmentioning
confidence: 93%
“…This, combined with reported resolution observed following treatment with systemic antibiotics, has lent support to the role of an altered microbiome in the development of granular parakeratosis. 3,[14][15][16] However, rare reports of congenital onset, and development of granular parakeratosis following administration of systemic medications, highlight that the exact pathogenesis remains elusive and is a subject that warrants further investigation. [17][18][19] Notably, our review highlights that findings of parakeratosis and retention of keratohyalin granules within the stratum corneum, despite its name, is not always present on histologic examination of granular parakeratosis.…”
Section: Discussionmentioning
confidence: 99%
“…As evidence, HS generally starts during puberty and often abates following menopause in women, with some women experiencing changes in disease activity in association with the menstrual cycle. Several studies of hormone‐targeting therapies have demonstrated improvement in HS in female patients . Based on these findings, spironolactone may be a potential therapy in females.…”
Section: Scientific Session 5: Medical Treatment Of Hidradenitis Suppmentioning
confidence: 90%